(untitled) (Al-Academy, 2016)
is divided into two chapter:Chapter one to ensure asyslematic framework for research amd included aresearch problem and also inchuded on the importance of research and the need for him as well as to clarify. The second chapter inchuded a theoretical framework: theoretical framework has been divided into two section. The first topic: poetics transformations The second topic: poetics and scale of rheloric in the film After the comp of the theoretical framework; so the researcher analyzed the film (Antichrist) has arrived ataset of resuits was including